2005
DOI: 10.1021/jp0451344
|View full text |Cite
|
Sign up to set email alerts
|

Protonated Serine Octamer Cluster:  Structure Elucidation by Gas-Phase H/D Exchange Reactions

Abstract: The H/D exchange kinetics of the protonated serine octamer was investigated by both flow-tube and FT-ICR experiments. The exchange was observed to be bimodal in agreement with previous observations. Quantitative analysis of the experimental results led to site-specific H/D exchange rate constants on the basis of which the structures of both ion populations were deduced. We observe the two separate conformers exchanging 33 hydrogens each-in an independent manner and at different rates. This result was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 26 publications
1
59
0
5
Order By: Relevance
“…[110,[132][133][134][135][136][137][138] Die ersten Versuche dieser Art ergaben, dass es mindestens zwei Isomere des protonierten Serinoctamers gibt; [134] dies wurde in späteren Untersuchungen bestätigt. [136,137] Wasserstoff/Deuterium-Austauschreaktionen von Serinoctameren wurden auch in einem Prototypen eines hochauflösenden Orbitrap-Massenspektrometers durchgeführt. Der Aufbau des Orbitrap [122] ermöglicht es, H/D-Austauschreaktionen an eingefangenen Ionen in der linearen Quadrupolfalle der Ionenführung vorzunehmen.…”
Section: Dissoziationunclassified
See 3 more Smart Citations
“…[110,[132][133][134][135][136][137][138] Die ersten Versuche dieser Art ergaben, dass es mindestens zwei Isomere des protonierten Serinoctamers gibt; [134] dies wurde in späteren Untersuchungen bestätigt. [136,137] Wasserstoff/Deuterium-Austauschreaktionen von Serinoctameren wurden auch in einem Prototypen eines hochauflösenden Orbitrap-Massenspektrometers durchgeführt. Der Aufbau des Orbitrap [122] ermöglicht es, H/D-Austauschreaktionen an eingefangenen Ionen in der linearen Quadrupolfalle der Ionenführung vorzunehmen.…”
Section: Dissoziationunclassified
“…Daher kann der Umfang der Austauschreaktion experimentell durch ¾nde-rung des Deuterierungsmittel-Partialdrucks und/oder der Reaktionsdauer gesteuert werden. Die Elektrospray-Massenspektren der H/D-Austauschreaktionen von Serinoctameren in einem FT-ICR- [135][136][137] und einem Orbitrap-Massenspektrometer [106,107,134] Diese H/D-Austauschreaktionen belegen, dass Serinoctamere in mindestens zwei isomeren Formen A und B vorkommen. [134][135][136][137] Aber nur das Konformer A zeigt Chiralitätseffekte (Details dazu finden sich in Lit.…”
Section: Dissoziationunclassified
See 2 more Smart Citations
“…Tandem mass spectrometry [38,41,56], ion mobility cross section measurements [36,40,41], theoretical calculations [38 -41, 45], and hydrogen/deuterium exchange reactions [47][48][49][57][58][59][60][61] have all been used to gain information about the structure(s) of serine clusters. These studies have demonstrated that there are two structural types of protonated serine octamers and that at least one is composed of zwitterionic monomers.…”
mentioning
confidence: 99%